Emotional State Features in Women Raising Children with Developmental Disorders - Elena S. Grinina (Peoples' Friendship University of Russia (RUDN University), 2019)
The article is devoted to the results of a theoretical and empirical study of the emotional state of the modern women raising children with developmental disorders. This subject is relevant not only in the context of the emotional health of modern women, but also in connection with close psychological interference of mother and child with developmental disorders. According to the modern literature these parents have specific emotional sphere and personality characterized by a prevalence of guilt, anxiety, changing of value system, self-deprecation, etc. The most relevant is the analysis of the level of stress and depression as significant indicators of not only the emotional well-being, but also the possibilities of activating and implementing the adaptation and mobilization mechanisms of the personality. A comparative empirical study of the emotional state was conducted in the women raising children with developmental disorders and women raising healthy children. In accordance with the PSM-25 Psychological Stress Measure and the Beck Depression Inventory there is a decrease in the manifestation of an acute reaction to stress factors, the chronization of stress state with a tendency of the transition of the emotional sufferings to a depressive phase in the women raising children with developmental disorders. The results of the "Sack's Sentence Completion Test" technique show that 80% of the answers of the mothers raising children with developmental disorders as "emotionally negative" whereas in the control sample "emotionally positive" answers prevail (85%). The data obtained in the course of empirical research allow us to state the expressed disruptiveness of the emotional condition of the women raising children with developmental disorders, the tendency to depression, mainly negative nature of emotional experiences, and chronic mental tension. The decrease in the level of stress in combination with higher rates of depression, demonstrates a decrease in the emotional adaptation potential of such women, the transition of experiences to a deeper, immobilizing level. The analysis of the research data suggests that it is necessary to start psychological support of mothers raising children with developmental disorders as early as possible, to develop adaptive ways of responding to a stressful situation, which will help prevent chronic stress and developing of a depression.